The storage stability of water-based dental luting cements in Manila based on measurements of compressive strengths - Dalipe, Pearl Joy F.
Dental luting cements are important in the field of fixed partial prosthodontics because it provides the link between the prepared tooth and the well-fabricated restoration. Unfortunately, the storage stability of dental luting cements is very much overlooked. Temperature and humidity levels in our country are high therefore making it difficult to store these cements at ideal storage conditions. Changes in physical and mechanical properties may not be clinically noticeable but these may affect the ultimate longevity of the restoration. An experimental study was conducted. Zinc Polycarboxylate and Compomer cement were used as samples. One group was stored in an airtight container in the lowest part of a refrigerator while another group was stored inside a cabinet at the Operative Dentistry section of UP College of Dentistry. Compressive strengths were measured at 0, VA, and TA months. Results show that there is no significant difference in the compressive strength of Zinc Polycarboxylate and Compomer cement from baseline to 21/z months of storage in Manila. There is also no significant difference between compressive strengths of Zinc Polycarboxylate and Compomer cement stored at room temperature and in the refrigerator.